A Ka-Band 4TX/4RX Dual-Stream Joint Radar-Communication Phased-Array CMOS Transceiver - Zhao, Fuyuan; Deng, Wei; Wu, Rui; Jia, Haikun; Wu, Qixiu; Xin, Jihao; Zeng, Zhiyuan; Li, Yanlei; He, Yejun; Wang, Zhihua; Chi, Baoyong (IEEE transactions on microwave theory and techniques, 2024)
A Ka-band 4TX/4RX dual-stream joint radar-communication phased-array transceiver is presented for the emerging radar-communication integrated wireless system. Different from the existing joint radar-communication transceiver with separated downconversion path and analog baseband, the proposed joint radar-communication transceiver features completely reused hardware components. In addition, various circuit design challenges in the joint radar-communication transceiver are addressed. In order to enhance the signal-to-noise and distortion ratio (SNDR) in low input power region for the communication mode and effectively reduce the chip area, a current-flopping bidirectional active mixer is proposed. A variable-transmission-line-based phase shifter (TL-PS) with tiling structure is introduced to achieve wideband phase shifting with flat group delay and in-band loss fluctuation. A pseudo-stacked power amplifier (PA) is introduced to provide both high linearity and high saturated output power for the joint radar-communication transceiver. A 4TX/4RX dual-stream joint transceiver is designed and fabricated in a standard 65-nm complementary metal-oxide-semiconductor (CMOS) process with the chip area of 16.2 mm2. The measured results show that the TRX covers 28.7-36.2 GHz with the peak gain of 22.2/34.7 dB for TX/RX. The measured TX peak saturated output power is 19.9 dBm and the OP _{1 dB} is 17.4 dBm. The measured RX minimum noise figure (NF) is 4.8 dB and the IP _{1 dB} is >-31.5 dBm. In addition, the analog baseband offers a 3.5-GHz bandwidth for the wideband radar signal. System measurement indicates that the proposed transceiver supports real-time centimeter-level 2-D imaging and 400-Msym/s 64-quadrature amplitude modulation (QAM) over-the-air (OTA) wireless link.